ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI STIKER DENGAN MENGGUNAKAN METODE HARGA POKOK PESANAN PADA CV. ESA MEDIA PROMO DI SAMARINDA - -, MAMBAUL ULUM (EKONOMIA, 2017)
Mambaul ulum, 2016, Title of thesis was â€œAnalysis of Cost of Production Stickers Calculation Using Base Price Method Order On CV Esa Media Promo in Samarindaâ€.The purpose of this study is to investigate and analyze the cost of production ofÂ  5,000 copies printed sticker on an order of costof goods produced by CV Esa Media Promo in Samarinda.Based on research, in determining the price of staple products the company only collect the cost of direct materials and direct labor costs actually happened is charged or counted directly against the order question, while factory overhead costs accounted for 30% of the total cost of raw materials, this causing errors in calculation of goods manufactured by the company. According to the theory of cost accounting. In calculating the cost of production, there are three cost components, namely : cost of raw materials, direct labor cost and factory overhead cost.The analytical tool used in this research is a method of collecting the cost of production by using cost of goods orders.Cost of goods manufactured by the company amounted Rp 17,644,000.00 and per-unit cost of good amounted Rp 3,532,80. Meanwhile, according to the result of the analysis, production cost is Rp 10,818,213.46 and cost of goods per unit on an order of cost of goods amounted to Rp 2,163.64.Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Based on the analysis that has been done to order stickers , can be the difference between the results of calculation of the cost of production based on cost accounting practices with the order cost method to the calculation of the cost of production according to the methods of the company.After testing the hypothesis by conducting calculation of the cost of production by using the order cost , it can be seen that the calculations performed by the company is higher than the calculation is by using the order cost method so the hypothesis is acceptedThis, the authors proposed the hypothesis can be accepted because there are difference in production costs resulting classification if cost of goods companies are not in accordance with the authorâ€™s calculations.